Analisis Hubungan antara Suku Bunga, Nilai Tukar, dan Jumlah Uang Beredar Terhadap Inflasi di Indonesia - Bahrur Rokhim; Aurel Rani Avidesta R; Dhenia Lizariani; Suci Hayati (Indonesia Economic Journal, 2025)
One of the economic problems that has received a lot of attention is inflation, because inflation is an important indicator in assessing the level of economic stability of a country. Inflation that occurs in a country can reduce people's purchasing power due to continuous price increases. Inflation can occur due to various factors, including the influence of interest rates, exchange rates, and the amount of money in circulation. This study aims to determine the effect of interest rates, exchange rates, and the amount of money in circulation on inflation in Indonesia. The research method used in this study is a qualitative method with data collection techniques sourced from various types of literature, such as journals, books, BPS and online sources (Google Scholar). The results of the study obtained are that interest rates have a positive and significant effect on inflation in Indonesia, exchange rates also have a positive and significant effect on inflation in Indonesia, and the amount of money in circulation has a positive but not significant effect on inflation in Indonesia. Simultaneously, these three aspects affect inflation in Indonesia.